2007
DOI: 10.1073/pnas.0707399104
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to CD4-induced sites in HIV gp120 correlate with the control of SHIV challenge in macaques vaccinated with subunit immunogens

Abstract: Epitopes located in and around the coreceptor binding site of HIV-1 envelope glycoprotein (gp120) exhibit enhanced exposure after attachment to the CD4 receptor and comprise some of the most conserved and functionally important residues on the viral envelope. Therefore, antibody responses to these epitopes [designated as CD4-induced (CD4i)] should be highly cross-reactive and potentially useful for HIV vaccine development. To address this question, rhesus macaques were vaccinated with subunit immunogens design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
109
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(118 citation statements)
references
References 37 publications
9
109
0
Order By: Relevance
“…Furthermore, passive administration of nmAbs to RMs has unambiguously been shown to provide protection against mucosal SHIV infection (5-13), with in vitro serum nAb IC 50 titers in the range of ∼1:200 emerging as predictive of protection (7,12,14). However, it was not known whether these low to moderate nAb titers would extend to vaccine-elicited antibody protection, as previous studies have reported a disconnect between in vitro nAb and a protective effect (33)(34)(35). Here, we directly demonstrate that prechallenge serum nAb titers against the autologous breakthrough T/F Env variants were not predictive of protection.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, passive administration of nmAbs to RMs has unambiguously been shown to provide protection against mucosal SHIV infection (5-13), with in vitro serum nAb IC 50 titers in the range of ∼1:200 emerging as predictive of protection (7,12,14). However, it was not known whether these low to moderate nAb titers would extend to vaccine-elicited antibody protection, as previous studies have reported a disconnect between in vitro nAb and a protective effect (33)(34)(35). Here, we directly demonstrate that prechallenge serum nAb titers against the autologous breakthrough T/F Env variants were not predictive of protection.…”
Section: Discussionmentioning
confidence: 74%
“…We make this speculation on our recent vaccine studies in rhesus macaques (epostersonline. com/aidsvax2013/?q=node/639 and http:// epostersonline.com/aidsvax2013/?q=node/ 645&posterview=true) using a conformationally constrained gp120 subunit immunogen (82,83). Taken together, the three ineffective Ad5-HIV trials strongly suggest the presence of CD4 + CCR5 + T cells at the area of transmission.…”
Section: Strategies To Elicit Continuous Protection Against Hiv By Vamentioning
confidence: 76%
“…The emergence of high ADCC titers in low to intermediate anti-C1 IgA responders as a correlate of decreased infection risk is one such example (25). Similarly, post hoc analyses of SHIV/SIV challenge studies using our conformationally constrained gp120 vaccine (82,83) in nonhuman primates revealed that humoral responses being equal, protection from acquisition was lowest or abrogated in rhesus macaques with the highest vaccine-elicited anti-Env T-cell responses (epostersonline. com/aidsvax2013/?q=node/639 and http:// epostersonline.com/aidsvax2013/?q=node/ 645&posterview=true).…”
Section: Approach To Solving the Antibody Persistence And T-cell Balamentioning
confidence: 99%
See 1 more Smart Citation
“…ELISAs were performed using an antigen-capture format (78) as described previously (68,79). ADCC Assays.…”
Section: Methodsmentioning
confidence: 99%